The development, implementation and evaluation of a short course in objective structured clinical examination (OSCE) skills - A. de Villiers; E. Archer (South African Family Practice)
Background: Objective structured clinical examination (OSCE) examiner training is widely employed to address some of the reliability and validity issues that accompany the use of this assessment tool. An OSCE skills course was developed and implemented at the Stellenbosch Faculty of Health Sciences and its influence on participants (clinicians) evaluated.